Medical-surgical nursing : critical thinking in client care - Lemone, Priscilla; Burke, Karen (New Jersey : Pearson Education, 2004)
It is built around functional health patterns, with a focus on developing decision-making skills through an abundance of case studies and examples. Includes new topics such as diseases specific to bioterrorism, information on diversity, and focused assessments with information specific to the older adult. Covers new concepts such as health promotion, home care with resources, and complementary therapies.
Part 1. Medical-Surgical Nursing Practice -- Part 2. Nutrition and Metabolic Patterns -- Part 3. Elimination Patterns -- Part 4. Activity and Exercise patterns -- Part 5. Cognitive and Perceptual Patterns -- Part 6. Sexuality and reproductive patterns.
Includes bibliographical references and index.
Keywords: NURSING